High-resolution insight into the competitive adsorption of heavy metals on natural sediment by site energy distribution. (April 2018) - Huang, Limin; Jin, Qiang; Tandon, Puja; Li, Aimin; Shan, Aidang; Du, Jiajie
Abstract: Investigating competitive adsorption on river/lake sediments is valuable for understanding the fate and transport of heavy metals. Most studies have studied the adsorption isotherms of competitive heavy metals, which mainly comparing the adsorption information on the same concentration. However, intrinsically, the concentration of each heavy metal on competitive adsorption sites is different, while the adsorption energy is identical. Thus, this paper introduced the site energy distribution theory to increase insight into the competitive adsorption of heavy metals (Cu, Cd and Zn). The site energy distributions of each metal with and without other coexisting heavy metals were obtained. It illustrated that site energy distributions provide much more information than adsorption isotherms through screening of the full energy range. The results showed the superior heavy metal in each site energy area and the influence of competitive metals on the site energy distribution of target heavy metal. Site energy distributions can further help in determining the competitive sites and ratios of coexisting metals. In particular, in the high-energy area, which has great environmental significance, the ratios of heavy metals in the competitive adsorption sites obtained for various competitive systems were as follows: slightly more than 3:1 (Cu-Cd), slightly less than 3:1 (Cu-Zn), slightly more than 1:1 (Cd-Zn), and nearly 7:2:2 (Cu-Cd-Zn). The results from this study are helpful to deeply understand competitive adsorption of heavy metals (Cu, Cd, Zn) on sediment. Therefore, this study was effective in presenting a general pattern for future reference in competitive adsorption studies on sediments. Graphical abstract: Image 1 Highlights: Site energy distribution was introduced to competitive adsorption on sediments. High-resolution insight into competitive adsorption on sediments was given. Shared adsorption sites can be determined by site energy distribution. Competitive metals can influence one another from site energy perspective. A new pattern for competitive adsorption analysis on sediments was presented.